KONSEP FISKAL ISLAM DALAM PERSPEKTIF HISTORIS - Ali Murtadho (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
Fiscal policy is not synonymous with Islam taxation / tribute that made the king / emperor , nor synonymous with modern fiscal policy born of the failure of the free market mechanism. Referring to public finance policy at the beginning of the Islamic era, Islamic fiscal policy is a practical representation of the mission of the Islamic economic system oriented religiosity , justice and wealth distribution.Not only deal with the fiscal revenue and expenditure of state revenue but also about the mission of fair distribution of wealth . Jizya, kharaj and ghanimah is a fiscal instrument in accordance with the circumstances at that time for the mission fair distribution of wealth . Based on the concept of fiscal Islam , then the application of fiscal policy now must somehow form could lead to a fair distribution of wealth towards a comprehensive community welfare ( falah ), not just the budget deficit